The Indonesian EFL Teachers' TPACK Development in the Online Community of Practice - Agustina Tyarakanita; Joko Nurkamto; Nur Arifah Drajati (State Institute for Islamic Studies IAIN of Metro, 2021)
This study sought to investigate teachers' TPACK level development after participating in a WhatsApp-based online community of practice (OCP) in Indonesia. This study addresses the issue of the teachers who are mandated to integrate technology in teaching. However, with a range of contexts, it is known that teachers lack confidence and competence in integrating technology. Therefore, a program for teachers that emphasizes theoretical and practice is one of the best solutions for improving their TPACK. A case study was adopted in this research. This study explored the practice process that took place in the OCP utilizing the notion of the community of practice (CoP) by Wenger (1998) and TPACK level by Niess (2015) to know the teachers' TPACK level development. The findings suggest that the TPACK level development was still not fully achieved by the teachers. This study recommends that the committee who designed the OCP carefully find the best way to make the teachers experience meaningful learning and achieve significant development on their TPACK.